NEEDS FOR THE PERFORMANCE ON THE CHILD DEVELOPMENT CENTER’S STANDARD UNDER THE LOCAL ADMINISTRATIVE ORGANIZATIONS IN BAN PHAI DISTRICT, KHON KAEN PROVINCE - Khantha, Nanthawan; Waroonroj, Jirawat (Journal of Buddhist Education and Research (JBER), 2022)
The purposes of this research were to study the current situation, the desirable conditions and the needs for the performance on the Child Development Center’s standard under the local administrative organizations in Ban Phai district, Khon Kaen Province. The sample group used for this research consisted of school administrators, teachers, and the child development center executive committees, with the total number of 155 people. The tool used for data collection was a 5-level rating scale questionnaire with 0.67-1.00 of content validity and 0.93 of the whole questionnaire reliability. The statistics used to analyze data comprised percentage, frequency, mean and PNI modified index. The research results were found that: The current situation in the performance on the child development center’s standard under the local administrative organizations in Ban Phai district, in overall, was found at a high level, when considering each aspect, it was found that the aspect with the highest average was teacher/caretaker provided caretaking and learning and playing experience management for child development, followed by the management of early childhood children development center and the quality of early childhood children of child development center, respectively. The desirable conditions, in overall, were found at the highest level, when considering each aspect, it was found that the aspect with the highest average was the quality of early childhood children of child development center, followed by the management of early childhood children development center and teacher/caretaker providing caretaking and learning and playing experience management for child development, respectively. Needs for the performance on the child development center’s standard under the local administrative organizations in Ban Phai district ranked according to the importance were as follows: 1) The quality of early childhood children of child development center. 2) The management of early childhood children development center. 3) Teacher/caretaker providing caretaking and learning and playing experience management for child development.